Influence of High Pressure or Autoclaving-Cooling Cycles and Pullulanase Treatment on Buckwheat Starch Properties and Resistant Starch Formation - Górecki Adrian R.; Błaszczak Wioletta; Lewandowicz Jacek; Le Thanh-Blicharz Joanna; Penkacik Kamila (Polish Journal of Food and Nutrition Sciences)
Buckwheat starch was subjected to cycles of high pressure-cooling (P-CC) or autoclaving-cooling (A-CC) combined with pullulanase debranching to determine changes in resistant starch (RS) content, digestibility, rheological properties and microstructure. Native buckwheat starch had 11.9 g/kg of RS, while the highest RS content (58.7 g/kg) was reached after A-CC and 6 h of pullulanase treatment. Among the P-CC samples, the highest RS content (43.3 g/kg) was obtained after treatment with 600 MPa/9 min and 6 h pullulanase debranching. The digestibility of the starch samples was negatively correlated with RS content and its highest values were noted for native and P-CC 200 MPa preparations subjected to 2 and 16 h of pullulanase treatment (95.18–95.35%). Buckwheat starch A-CC preparations after 6 h of pullulanase treatment exhibited the lowest digestibility (85.87%). Rheological analysis of 6% starch pastes showed that all investigated samples demonstrated a non-Newtonian flow, pseudoplastic properties and thixotropy. The Ostwald de Waele rheological model was very well fitted to the flow curves of the investigated pastes (R2>0.98). Both P-CC and A-CC reduced the consistency coefficient (K) and thixotropy values, while the flow behavior index (n) was increased only after P-CC treatment. The P-CC and A-CC treatment resulted in starch granule breakdown and porous gel structure formation, differing in surface properties.